2019
DOI: 10.3389/fnut.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Isolate Supplementation While Endurance Training Does Not Alter Cycling Performance or Immune Responses at Rest or After Exercise

Abstract: This study examined whey protein isolate supplementation combined with endurance training on cycling performance, aerobic fitness and immune cell responses. Eighteen male cyclists were randomly assigned to either placebo (PLA) or whey protein supplementation (WS; 1.0 g·kg body mass −1 ·d −1 in addition to their dietary intake). Both groups completed the identical endurance training program, 4 days per week for 6 weeks. Blood samples were obtained at rest and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
(65 reference statements)
3
9
0
Order By: Relevance
“…However, an almost identical study by Jonvik et al found no difference in these outcomes besides a trend indicating greater increases in leg lean mass for PRO compared to isocaloric CHO (15). These results were similar to the ndings of Forbes et al, demonstrating no difference between PRO (1.0 g kg -1 d -1 ) and isocaloric CHO following six weeks of cycling training (18). In contrast to the two previous trials, Roberson et al recruited runners who received either whey PRO (post training + pre sleep) or a noncaloric placebo pill while they underwent a 10-week progressive running program (17).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, an almost identical study by Jonvik et al found no difference in these outcomes besides a trend indicating greater increases in leg lean mass for PRO compared to isocaloric CHO (15). These results were similar to the ndings of Forbes et al, demonstrating no difference between PRO (1.0 g kg -1 d -1 ) and isocaloric CHO following six weeks of cycling training (18). In contrast to the two previous trials, Roberson et al recruited runners who received either whey PRO (post training + pre sleep) or a noncaloric placebo pill while they underwent a 10-week progressive running program (17).…”
Section: Introductionsupporting
confidence: 73%
“…Previous studies, have compared intake of PRO supplementation to an isocaloric CHO beverage (15,16,18) or a <1g sugar pill (17), showing contradicting results in relation to VO 2max and performance tests. One study found PRO to elicit greater increases in VO 2max , 10K TT and lean body mass (16) , while others have found no effect (15,18), or increased lean mass and a trend towards greater 5K TT in placebo (17). Hence, more research is needed to clarify whether PRO supplementation pre and post exercise may have bene cial effects on sports performance.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies, have compared intake of PRO supplementation to an isocaloric CHO beverage [14,15,17] or a < 1 g sugar pill [16], showing contradicting results in relation to VO 2max and performance tests. One study found PRO to elicit greater increases in VO 2max , 10 K TT and lean body mass [15], while others have found no effect [14,17], or increased lean mass and a trend towards greater 5 K TT in placebo [16]. Hence, more research is needed to clarify whether PRO supplementation pre and post exercise may have beneficial effects on sports performance.…”
Section: Influence Of Carbohydrate Intake On Training-induced Mitochomentioning
confidence: 96%
“…First, assuming that increases in endurance exercise volume with longer-distance endurance training necessitate the intake of more dietary protein, lower-volume HIIT may not result in the same increase in protein intake needs. Additionally, while 10 weeks of BCAA supplementation (12 g/d) has been shown to increase Wingate peak power and time trial performance in male cyclists [163], there are equivocal data demonstrating that protein supplementation during 6-10 weeks of endurance training fails to promote meaningful improvements in VO 2 peak [164,165], run time performance, cycling time performance [164] or markers suggestive of increased mitochondrial biogenesis [165,166]. While beyond the scope of this review, some of these studies call to question increased protein needs in endurance athletes (e.g., 1.8 g/kg/d) given that participants in non-protein supplemented groups who experienced similar exercise adaptations reported consuming~1.1-1.3 g/kg protein per day [165,166].…”
Section: Protein and Essential Amino Acidsmentioning
confidence: 99%